A systematic examination of the mucous membrane of the mouth (oral mucous membrane) - method of early diagnosis of precancerous diseases - Irina K. Lutskaya (LLC "MEDIAFORMAT", 2021)
The article presents information on the liability of the dentist for reducing the risk of development of pathological processes, including malignant neoplasms of the oral cavity. A thorough inspection of the oral mucous membrane, in accordance with WHO recommendations provides a systematic survey of all departments of the oral cavity and surrounding tissues. This tactic can significantly reduce the risk of development of pathological lesions of the oral cavity, to prevent malignant transformation or provide early diagnosis.